Airway bacteria measured by quantitative polymerase chain reaction and culture in patients with stable COPD: relationship with neutrophilic airway inflammation, exacerbation frequency, and lung function - Bafadhel M; Haldar K; Barker B; Patel H; Mistry V; Barer MR; Pavord ID; Brightling CE (International Journal of COPD, 2015)
Mona Bafadhel,1 Koirobi Haldar,2 Bethan Barker,2,3 Hemu Patel,4 Vijay Mistry,2,3 Michael R Barer,2–4 Ian D Pavord,1 Christopher E Brightling2,3 1Respiratory Medicine Unit, Nuffield Department of Clinical Medicine, University of Oxford, Oxford, UK; 2Department of Infection, Immunity and Inflammation, University of Leicester, 3Institute for Lung Health, National Institute for Health Research Respiratory Biomedical Research Unit, Glenfield Hospital, University of Leicester, 4Department of Clinical Microbiology, University Hospitals of Leicester NHS Trust, Leicester, UK Background: Potentially pathogenic microorganisms can be detected by quantitative real-time polymerase chain reaction (qPCR) in sputum from patients with COPD, although how this technique relates to culture and clinical measures of disease is unclear. We used cross-sectional and longitudinal data to test the hypotheses that qPCR is a more sensitive measure of bacterial presence and is associated with neutrophilic airway inflammation and adverse clinical outcomes.Methods: Sputum was collected from 174 stable COPD subjects longitudinally over 12 months. Microbial sampling using culture and qPCR was performed. Spirometry and sputum measures of airway inflammation were assessed.Findings: Sputum was qPCR-positive (>106 copies/mL) in 77/152 samples (Haemophilus influenzae [n=52], Moraxella catarrhalis [n=24], Streptococcus pneumoniae [n=19], and Staphylococcus aureus [n=7]). Sputum was culture-positive in 50/174 samples, with 49 out of 50 culture-positive samples having pathogen-specific qPCR bacterial loads >106 copies/mL. Samples that had qPCR copy numbers >106/mL, whether culture-positive or not, had increased sputum neutrophil counts. H. influenzae qPCR copy numbers correlated with sputum neutrophil counts (r=0.37, P<0.001), were repeatable within subjects, and were >106/mL three or more times in 19 patients, eight of whom were repeatedly sputum culture-positive. Persistence, whether defined by culture, qPCR, or both, was associated with a higher sputum neutrophil count, lower forced expiratory volume in 1 second (FEV1), and worsened quality of life.Interpretation: qPCR identifies a significant number of patients with potentially bacteria-associated neutrophilic airway inflammation and disease that are not identified by traditional culture-based methods. Keywords: H. influenzae, qPCR, sputum